Effect of structural characteristics of corncob hemicelluloses fractionated by graded ethanol precipitation on furfural production. (20th January 2016) - Li, Huiling; Dai, Qingqing; Ren, Junli; Jian, Longfei; Peng, Feng; Sun, Runcang; Liu, Guoliang
Highlights: The influence of characteristics of corncob hemicelluloses on furfural was studied. The hemicelluloses structure obtained by a graded ethanol precipitation was studied. A heterogeneous catalysis process in a biphasic system was employed. High xylose content, high M w / M n and crystallinity contributed to furfural production. 45.84% furfural yield was obtained from HO30 . Abstract: In the present study, a graded ethanol precipitation technique was employed to obtain hemicelluloses from the alkali-extracted corncob liquid. The relationship between the structural characteristics of alkali-soluble corncob hemicelluloses and the production of furfural was investigated by a heterogeneous process in a biphasic system. Results showed that alkali-soluble corncob hemicelluloses mainly consisted of glucuronoarabinoxylans andl -arabino-(4- O -methylglucurono)-d -xylans, and the drying way had less influence on the sugar composition, molecular weights and the functional groups of hemicelluloses obtained by the different ethanol concentration precipitation except for the thermal property, the amorphous structure and the ability for the furfural production. Furthermore, alkali-soluble corncob hemicelluloses with higher xylose content, lower branch degree, higher polydispersity and crystallinity contributed to the furfural production. A highest furfural yield of 45.41% with the xylose conversion efficiency of 99.06% and the furfural selectivity of 45.84% was obtained from the oven-dried hemicelluloses precipitated at the 30% (v/v) ethanol concentration.